Flow patterns and boundary conditions for inlet and outlet conduits of large pump system with low head - 徐磊 陆伟刚 陆林广 董雷 王兆飞 (Applied mathematics and mechanics, 2014)
The flow patterns in the inlet and outlet conduits have a decisive effect on the safe, stable, and highly efficient operation of the pump in a large pumping station with low head. The numerical simulation of three-dimensional （3D） turbulence flow in conduits is an important method to study the hydraulic performance and conduct an optimum hydraulic design for the conduits. With the analyses of the flow patterns in the inlet and outlet conduits, the boundary conditions of the numerical simulation for them can be determined. The main obtained conclusions are as follows： （i） Under normal operation conditions, there is essentially no pre-swirl flow at the impeller chamber inlet of an axial-flow pump system, based on which the boundary condition at the inlet conduit may be defined. （ii） The circulation at the guide vane outlet of an axial-flow pump system has a great effect on the hydraulic performance of the outlet conduit, and there is optimum circulation for the performance. Therefore, it is strongly suggested to design the guide vane according to the optimum circulation. （iii） The residual circulation at the guide vane outlet needs to be considered for the inlet boundary condition of the outlet conduit, and the value of the circulation may be measured in a specially designed test model.